A discrete Stochastic Korovkin theorem - George A. Anastassiou (International Journal of Mathematics and Mathematical Sciences)
In this article we give a sufficient condition for the pointwise −− in the first mean Korovkin property on B0(P), the space of stochastic processes with real state space and countable index set Γ and bounded first moments.